IgA vasculitis in patients with inflammatory bowel disease: new insights into the role of TNF-α blockers. (24th August 2021) - Rasmussen, Camille; Abitbol, Vered; El Karoui, Khalil; Bourrier, Anne; Paule, Romain; Vuitton, Lucine; Maurier, François; Laharie, David; Fuméry, Mathurin; Agard, Christian; Collins, Michael; Nancey, Stephane; et al.
Abstract: Objective: The association of IgA vasculitis (IgAV) and IBD is rarely described, mainly during anti-TNF-α therapy. We aimed to describe the association of IgAV and IBD. Methods: We retrospectively analysed the association of IgAV and IBD through the implication of the GETAID and FVSG networks. Characteristics of IBD and IgAV were collected using a standardized case report form. Results: Forty-three cases were included. IBD [mainly Crohn's disease (CD) in 58%] preceded IgAV in 38 (88%), with median interval of 9.2 (IQR 5.4–15.4) years. In these 38 patients, at IgAV diagnosis, five (13%) had active IBD and 28 (74%) were treated with anti-TNF-α for a median duration of 31.5 (IQR 19–56) months. Main IgAV manifestations were purpura all patients (100%), joints in 20/35 (57%), renal in 15/35 (43%) and gastrointestinal in 11/35 (31%) involvement. IgAV was treated with glucocorticoids in 25 (66%), colchicine in six (16%), CYC in six (16%) and anti-TNF-α were discontinued in 15/28 (54%). No IgAV relapse occurred when TNF-α blockers were stopped, vs 23% in patients pursuing it. Conversely, five (33%) had IBD flare or complication after anti-TNF-α cessation vs one (8%) in those continuing biologics. Anti-TNF-α were resumed in six (40%), with subsequent IgAV relapse in four (67%). Conclusions: This large cohort suggests that TNF-α blockers may promote the onset of IgAV in IBD. Discontinuation of anti-TNF-α was associated with vasculitis remission but increased risk of IBD relapses, whereas continuation of anti-TNF-α was associated with IBD remission but vasculitis relapse.